2014
DOI: 10.1007/s10704-014-9952-6
|View full text |Cite
|
Sign up to set email alerts
|

Observation of fracture sealing in high-strength and ultra-low-permeability concrete by micro-focus X-ray CT and SEM/EDX

Abstract: Fracture sealing by precipitation is known to occur in high-strength and ultra-lowpermeability concrete (HSULPC) immersed in water. Because a high ability to retard radionuclide migration is required for HSULPC, understanding both the sealing process and the composition of sealing deposits is important to identify optimum conditions for significant sealing. In this study, sealing of a macro-fractured HSULPC specimen with initial aperture of approximately 0.1 mm was investigated in simulated seawater over 49 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Its application to engineering fields such as geomechanics is becoming popular as high-resolution industrial micro-computed tomography systems are more widely available. For example, CT imaging has been used to characterize the internal structure of geomaterials such as soil (Elyeznasni et al 2012;Garbout et al 2013;Hapca et al 2015;Otani et al 2001), rock (Huang et al 2013;Huang and Xia 2015;Ito et al 2001;Liu et al 2014b;Sugawara et al 2004;Vervoort et al 2004), concrete (Darma et al 2013;Fukuda et al 2014;Henry et al 2014), and asphalt (Liu et al 2014a;Masad and Kassem 2009;Taniguchi et al 2012;Tomoto and Moriyoshi 2009). In this paper, the Brazilian disc (BD) sample is adopted to measure the dynamic tensile strength of rock materials (Zhou et al 2012) under hydrostatic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Its application to engineering fields such as geomechanics is becoming popular as high-resolution industrial micro-computed tomography systems are more widely available. For example, CT imaging has been used to characterize the internal structure of geomaterials such as soil (Elyeznasni et al 2012;Garbout et al 2013;Hapca et al 2015;Otani et al 2001), rock (Huang et al 2013;Huang and Xia 2015;Ito et al 2001;Liu et al 2014b;Sugawara et al 2004;Vervoort et al 2004), concrete (Darma et al 2013;Fukuda et al 2014;Henry et al 2014), and asphalt (Liu et al 2014a;Masad and Kassem 2009;Taniguchi et al 2012;Tomoto and Moriyoshi 2009). In this paper, the Brazilian disc (BD) sample is adopted to measure the dynamic tensile strength of rock materials (Zhou et al 2012) under hydrostatic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…An example is shown in Figure . Fukuda et al studied the healing efficiency in the interior of the crack of ultrahigh performance concrete when being exposed to seawater by SEM/EDX analysis. SEM/EDX was performed on a surface sawn orthogonal to the crack to determine the composition of the sealing deposits, as shown in Figure .…”
Section: Healing Efficiencymentioning
confidence: 99%
“…Note that cps indicates count per second. Reproduced with permission . Copyright 2014, Springer Nature.…”
Section: Healing Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Atkinson (1984) clarified the effects of the surrounding environment on subcritical crack growth in HSULPC, under various environmental conditions. Fukuda et al (2012Fukuda et al ( , 2013Fukuda et al ( , 2014 observed the self-sealing of cracks and pores in HSULPC in water using micro-focus X-ray computed tomography (CT) and reported that self-sealing occurred by the precipitation of Ca compounds.…”
Section: Introductionmentioning
confidence: 99%